The Impact of Purposeful Management on the Relationship between Organizational Conflict and Team Proactivity - Alagele , Hussain K. Hussain; Neama , Nagham H.; alkaseer, Natalya ahmed; Al Dulaimi, Haidar Ali; Abd, Sanaa Eesee (Journal of Ecohumanism, 2025)
Higher education is considered one of the important institutions that contribute to providing other institutions with energies, expertise and efficiency due to its energies, human resources and various specializations. Therefore, it is considered the vital artery, which is what made it a subject of great interest. There are some challenges that must be faced. This study focused on three main variables: team proactivity, purposeful management and organizational conflict. A random sample of higher education workers from various universities was taken. Data was collected through a questionnaire and (310) questionnaires were distributed. (235) of them were suitable for analysis. The data were analyzed using the (SPSS) programs version 25, where to analyze the relationship and influence between the three variables. The results showed that there is a positive significant relationship between organizational conflict and team proactivity and that purposeful management has a direct and indirect impact on organizational conflict. team proactivity.